2005
DOI: 10.1681/asn.2004070602
|View full text |Cite
|
Sign up to set email alerts
|

Serum Phosphate Levels and Mortality Risk among People with Chronic Kidney Disease

Abstract: Elevated serum phosphate levels have been linked with vascular calcification and mortality among dialysis patients. The relationship between phosphate and mortality has not been explored among patients with chronic kidney disease (CKD). A retrospective cohort study was conducted from eight Veterans Affairs' Medical Centers located in the Pacific Northwest. CKD was defined by two continuously abnormal outpatient serum creatinine measurements at least 6 mo apart between 1999 and 2002. Patients who received chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
767
5
24

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,075 publications
(826 citation statements)
references
References 28 publications
30
767
5
24
Order By: Relevance
“…Russo et al established in a cohort of predialysis patients that higher phosphorus levels were associated with CAC progression (55). Another study performed in CKD patients observed an association between higher phosphorus levels and mortality (56). Again, hypotheses generated by observational studies require testing in randomized trials, in order in this case to assess the impact of phosphate binders on survival or AoC progression (57).…”
Section: Discussionmentioning
confidence: 99%
“…Russo et al established in a cohort of predialysis patients that higher phosphorus levels were associated with CAC progression (55). Another study performed in CKD patients observed an association between higher phosphorus levels and mortality (56). Again, hypotheses generated by observational studies require testing in randomized trials, in order in this case to assess the impact of phosphate binders on survival or AoC progression (57).…”
Section: Discussionmentioning
confidence: 99%
“…Visceral myocardial calcification may enhance the risk of arrhythmic events and sudden death. Phosphate excess may increase circulating parathyroid hormone (PTH) and/or decrease 1,25-dihydroxyvitamin D levels (6). Hyperparathyroidism is associated with cardiovascular disease (6).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate excess may increase circulating parathyroid hormone (PTH) and/or decrease 1,25-dihydroxyvitamin D levels (6). Hyperparathyroidism is associated with cardiovascular disease (6). Animal studies of experimental renal failure have linked PTH excess to intracellular calcium overload, cardiac fibrosis, and impaired myocardial energy production (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[97][98][99][100][101] Non-calcium-based phosphate binders may correct hyperphosphatemia and ameliorate abnormalities of the mineral metabolism associated with accelerated kidney disease progression and increased cardiovascular risk. [102][103][104] The finding that phosphate binders reduced proteinuria, an effect that appears to be associated with significant renoprotection in the long term according to recent animal studies (Fig 2), 105,106 along with results of the post hoc analysis of the REIN Study, 51 can be taken to suggest that strategies aimed at lowering phosphate levels might be used in the future to maximize the renoprotective effects of RAAS-blocking agents.…”
Section: Insights From Recent Experimental Studies and Novel Therapeumentioning
confidence: 97%